2014
DOI: 10.1007/s00417-014-2881-2
|View full text |Cite
|
Sign up to set email alerts
|

Refractive and visual outcomes after combined cataract and trabectome surgery

Abstract: Refractive and visual outcomes were similar in both groups. Despite the slightly higher rate of postoperative macula edema, we were able to observe that the combination of these two procedures is a feasible method in glaucoma and cataract surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Another advantage of MIGS strategies is a reduced risk of a large refractive surprise compared to conventional filtering operations and faster visual rehabilitation. 17 Sieck et al concluded that there were no difference found between the refractive outcomes of glaucoma patients with or without KDB. 18 Also, in 2020 a study result that iStent inject does not risk refractive outcomes and can be paired with cataract procedure safely.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of MIGS strategies is a reduced risk of a large refractive surprise compared to conventional filtering operations and faster visual rehabilitation. 17 Sieck et al concluded that there were no difference found between the refractive outcomes of glaucoma patients with or without KDB. 18 Also, in 2020 a study result that iStent inject does not risk refractive outcomes and can be paired with cataract procedure safely.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that scleral IOL fixation results in more lens tilt than regular cataract surgery with in-the-bag-placement of the IOL [27, 28]. One could well imagine that instability could be worsened in MFS eyes in general by the weakened tissue itself and by damaged ocular structures from trauma or chronic inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Luebke et al showed, in a retrospective review of 137 patients at the University Eye Hospital in Freiburg, Germany, that visual outcomes were not statistically different in patients that had cataract surgery with and without Trabectome; however, the rate of cystoid macula edema was slightly higher (2.2% in combined surgery vs 1.9% in cataract surgery alone). 20 In the reported studies here, 9 12 , 14 , 15 , 17 , 18 there have been no reports of infection, choroidal effusion, choroidal hemorrhage, or wound leaks.…”
Section: Increasing Trabecular Flowmentioning
confidence: 68%